Highly Transparent and Conductive Indium‐Free Vanadates Crystallized at Reduced Temperature on Glass Using a 2D Transparent Nanosheet Seed Layer. (9th September 2021) - Boileau, Alexis; Hurand, Simon; Baudouin, Florent; Lüders, Ulrike; Dallocchio, Marie; Bérini, Bruno; Cheikh, Aimane; David, Adrian; Paumier, Fabien; Girardeau, Thierry; Marie, Philippe; Labbé, Christophe; et al.
Abstract: Indium‐tin‐oxide (ITO) is a widely employed transparent conducting oxide (TCO), but the indium scarcity and price encourage developing some alternatives. The correlated metals CaVO3 and SrVO3 have been recently identified as new TCOs with functional properties being comparable to ITO. However, their technological potential is limited by the critical requirement of a perovskite structure of the film, impossible to achieve via direct growth on substrates commonly used for applications. In this article, the authors tackle this limitation by demonstrating the crystalline growth of vanadate TCOs on glass at temperatures below 600 °C, with the help of 2D nanosheets as transparent seed layers. The functional properties do not suffer from the textured structure of the films, as confirmed by an in‐depth spectroscopic ellipsometry study, allowing for an industrially viable approach to integrate vanadate TCOs on virtually any surface and to exploit their promising performances as a new generation TCO. Abstract : The integration of a new class of transparent conductor oxides (TCOs) based on a vanadate perovskite structure is achieved using a 2D transparent nanosheet template layer on glass at low temperature. This work provides a complete description of the heterostructure by morphological, structural, electrical, and optical analyses and opens new perspectives for the integration of complex indium‐free TCOs onto non‐adapted substrates.